(untitled) (Zien Journal of Social Sciences and Humanities, 2026)
This article discusses the factors that negatively affect the consciousness of young people as a result of the expansion of the information space in the context of globalization, including mass culture, moral degradation, and the penetration of foreign ideas. The article substantiates the priority areas of development of the spiritual and educational sphere in New Uzbekistan, the need to preserve national values, and strengthen the spiritual immunity of young people. The importance of studying foreign experience and adapting it to national conditions is also scientifically analyzed